Pengaruh ROA, Inflasi dan Nilai Tukar Rupiah Terhadap Harga Saham Syariah Sektor Industri Barang Konsumsi Perusahaan Terindeks ISSI 2019-2022 - Arifa, Denissa; Ningsih, Endang; Amaroh, Siti (Journal of Applied Islamic Economics and Finance, 2024)
This study was made to analyze the influence of ROA, inflation, and rupiah exchange rate on sharia stock prices sector consumer goods industry ISSI indexed companies 2019-2022. The share prices in this study are the share prices of companies in the consumer goods industry sector which have consistently been indexed on ISSI from December 2019 to December 2022. The sample consists of 31 companies. All data was obtained from the official websites of the Indonesia Stock Exchange, Bank Indonesia, and the Central Bureau of Statistics. This research method is quantitative with data analysis techniques using classic assumption tests and hypothesis testing, with SPSS version 16.0. The results of this study are: ROA has a partial and significant effect on stock prices, while partially inflation and the rupiah exchange rate have no significant effect on stock prices. Simultaneously ROA, inflation, and the rupiah exchange rate have a significant effect on stock prices.